THE ABSENCE OF MOTHER: THE RELATIONSHIP OF FATHER DAUGHTER IN GOTHIC FICTIONS - Ayu, Hujuala Rika (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2017)
This paper discusses the bonding of father and daughter in Angela Carters œThe Courtship of Mr. Lyon and Intan Paramadithas œPintu Merah (transl. œThe Red Door). Carter and Paramaditha employ distinguished narrative structures to highlight the interaction among the characters. They utilizes third-person narrator and reproduces fairy tales. The absence of mother becomes an interesting pivot in both stories. In that situation, father is inevitably the daughters closest figure. In both stories, fathers are at the same time demanding and lame. While, daughters are those dependent, submissive yet tactical figures in facing their fathers as the sole counterparts in the story. Using the perspectives of Juliett Michelle and Nancy Chodorow on psychoanalysis feminism, this paper unveils the roles of father in daughters adolescent development. This study reveals that despite the dependencies of the daughters toward the familial relationship, they use their submissiveness as the weapons to break the patriarchal values represented by the fathers.